The Consequences of a Heart Condition: Acute Stroke and Limb Ischemia Secondary to Massive Intracardiac Thrombus in a Young Female with Dilated Cardiomyopathy - Lestari, Defyna Dwi; Tjahjono, Cholid Tri; Kurnianingsih, Novi (Universitas Brawijaya, 2024)
Background :Dilated cardiomyopathy (DCM) is associated with the increased occurrence of left ventricular (LV) thrombosis caused by cardiac dysfunction. This condition is associated with significant mortality and morbidity because of its significance as a potential source of systemic emboli. We are reporting a case of Acute Stroke and Limb Ischemia in a Young Female Patient with DCM.Case Illustration :A 20-year-old female was referred to our hospital due to pain in her right lower extremities and weakness in her right limb. She had been diagnosed with peripartum cardiomyopathy five years earlier. A general physical examination found her right lower limbs to be cold and pulseless. A neurological examination revealed hemiparesis involving the right side of her body. The chest radiograph showed cardiomegaly. Electrocardiography indicated sinus rhythm with LVH. The transthoracic echocardiograms revealed significant LV systolic failure with a massive thrombus at LV. The Duplex ultrasound showed a thrombus at the right dorsal pedis artery, and a head CT scan revealed an acute infarct. The patient was started on heparin and bridged with warfarin 5mg orally daily, and she was uneventfully discharged after one week.Conclusion :DCM had been associated with thrombosis, stroke, and an increased risk of thromboembolism. Previous studies had documented decreased thromboembolic events due to administering anticoagulants.